1995
DOI: 10.1002/elan.1140071205
|View full text |Cite
|
Sign up to set email alerts
|

Redox kinetics in cathodic stripping square‐wave voltammetry

Abstract: Several redox systems with reactants which are immobilized at the electrode surface (EuSal complex, SeIV and Se" in the presence of Cu", cysteine and p-nitrophenol) were studied by square-wave voltammetry to examine whether their redox kinetics can be measured by using the phenomenon of the 'quasireversible maximum'. This is explained in detail. The following standard rate constants are obtained:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…If by increasing the scan rate the parameter h decreases from 3 to 0.3, the response changes its appearance from reversible to quasireversible and the peak currents recorded in very thin cells may increase exponentially. Similar kinetic maxima were observed in square-wave voltammetry of some surface redox reactions [25]. 4 (1,3,4), and 0.6 (2,5).…”
Section: Modelsupporting
confidence: 76%
“…If by increasing the scan rate the parameter h decreases from 3 to 0.3, the response changes its appearance from reversible to quasireversible and the peak currents recorded in very thin cells may increase exponentially. Similar kinetic maxima were observed in square-wave voltammetry of some surface redox reactions [25]. 4 (1,3,4), and 0.6 (2,5).…”
Section: Modelsupporting
confidence: 76%
“…The most remarkable properties of the quasireversible electrode mechanism of an adsorbed redox couple are the splitting of the SW response under large signal amplitude [38] and the quasireversible maximum [34,[36][37][38][39]. In the present mechanism, both properties exhibit an appreciable sensitivity to the surface follow-up chemical reaction, whereas they are virtually insensitive to the volume chemical reaction, and hence provide simple diagnostic criteria for distinguishing the type of the following chemical reaction.…”
Section: Quasireversible Casementioning
confidence: 99%
“…It is manifested as a parabolic dependence of the dimensionless net peak current on the redox kinetic parameter of the respective electrode reaction. The origin and the applicability of the quasireversible maximum for redox kinetic measurements have been thoroughly elaborated in a series of previous studies [34,[36][37][38][39][40][41][42]. In the recent work [27], it has been demonstrated that the volume chemical reaction has no influence on the position of the quasireversible maximum for the EC mechanism of the adsorbed redox couple.…”
Section: Quasireversible Casementioning
confidence: 99%
“…The reduction of electrodeposited copper selenide belongs to the group of redox reactions with immobilized reactants [22].…”
Section: Resultsmentioning
confidence: 99%